Land security and crop theft in rural Tanzania - Ochieng, Nelson A.; Grote, Ulrike; Basu, Arnab K. (PLOS ONE, 2026)
Is the risk of agricultural crime victimization linked to land titling and different land tenure modes? Drawing on a unique household survey from rural Tanzania, we find that farmers cultivating individually-owned plots are more likely to experience victimization, such as theft and vandalism of staple crops, compared to those operating on family-owned plots. Moreover, land titling has a negative effect on crime victimization. Our results remain robust under several empirical strategies, namely double lasso logistic regression and a linear probability model, as well as propensity score matching and an inverse probability-weighted regression. The findings offer policy relevant insights for enhancing land security and reducing agricultural crime in rural settings.